general formula to factor the difference of perfect squares:
A^2 - B^2 = (A + B) (A -B)
36 Y^2 = (6Y)^2
25 A^2 = (5A)^2
so the answer is (6Y + 5A) (6Y - 5A)
2007-01-14 13:16:37
·
answer #1
·
answered by davidosterberg1 6
·
0⤊
0⤋
36y^2 - 25a^2
= (6y)^2 - (5a)^2
= (6y - 5a) . (6y + 5a)
(Difference of Perfect Squares)
2007-01-14 20:34:40
·
answer #2
·
answered by Scarlet Manuka 7
·
0⤊
0⤋
36y^2 - 25a^2 = (6y - 5a)(6y + 5a)
2007-01-14 20:56:59
·
answer #3
·
answered by Sherman81 6
·
0⤊
0⤋
(6y+5a)(6y-5a) Do your own math!
2007-01-14 20:46:13
·
answer #4
·
answered by Burton Dude 2
·
0⤊
0⤋
36y^2-25a^2
=(6y)^2-(5a)^2
=(6y+5a)(6y-5a)
s
2007-01-14 20:53:28
·
answer #5
·
answered by alpha 7
·
0⤊
0⤋
(6y-5a)(6y+5a)
2007-01-14 21:40:10
·
answer #6
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
(6y-5a)(6y+5a)
2007-01-14 20:31:45
·
answer #7
·
answered by zephrrrrrrrrrrr 2
·
0⤊
0⤋